Three-year outcomes after high hyperopia correction using photorefractive keratectomy with a large ablation zone - Kaluzny, Bartlomiej J.; Piotrowiak-Slupska, Ilona; Kaszuba-Modrzejewska, Magdalena; Stachura, Joanna; Arba Mosquera, Samuel; Verma, Shwetabh (British journal of ophthalmology, 2019)
Aim To evaluate refractive and visual outcomes of photorefractive keratectomy (PRK) to treat high hyperopia using an aberration-neutral profile and large ablation zone. - Methods This was a retrospective, consecutive observational case series at the Oftalmika Eye Hospital, Bydgoszcz, Poland. We included 51 consecutive eyes of 34 patients who underwent alcohol-assisted PRK to correct hyperopia within the range of +3.6 to +6.15 D (mean+4.61±0.67 D). Procedures were performed with an Amaris 750S excimer laser (Schwind eye-tech-solutions GmbH, Kleinostheim, Germany) using an aberration-neutral profile and a 10 mm total ablation zone. Refractive results, predictability, safety and efficacy were evaluated 3 years postoperatively. - Results At 1-year postsurgery, the mean manifest refraction spherical equivalent (MRSE) was −0.002±0.43 D and mean cylinder was −0.181±0.31 D, while the values were +0.09±0.46 D and −0.15±0.26 D, respectively, at 2 years (MRSE p<0.001) and +0.15±0.44 D and −0.15±0.26 D, respectively, at 3 years (MRSE p<0.001). 78% of eyes were within ±0.50 D of the attempted spherical equivalent correction. Three years postoperatively, 22% of eyes lost one line of corrected distance visual acuity and 27% gained a line or two. The change in the mean corneal spherical aberrations for the 6 mm zone was from 0.27±0.07 to 0.08±0.13 µm. - Conclusions High hyperopia correction with PRK using an aberration-neutral profile and large ablation zone provides good efficacy, safety, predictability and visual outcomes. Relatively low change of corneal spherical aberrations and low increase of hyperopia in the first three postoperative years were observed.